Biological Control Effect of Antagonistic Bacteria on Potato Black Scurf Disease Caused by Rhizoctonia solani - Qingqing Lan; Yang Liu; Rongrong Mu; Xuetao Wang; Qian Zhou; Rehmat Islam; Xu Su; Yongqiang Tian (Agronomy, 2024)
Potato black scurf, caused by Rhizoctonia solani, is a severe soil-borne disease that affects the quality and production of potatoes worldwide. In our study, we used Paenibacillus polymyxa YF and Bacillus amyloliquefaciens HT to determine the antagonistic ability of R. solani, with a particular focus on the antagonistic action of P. polymyxa YF to R. solani and its biocontrol effect on potato black scurf. In fermentation, filtrate assay, 50% filtrate of P. polymyxa YF and B. amyloliquefaciens HT inhibited the growth of R. solani by 85.55% and 82.86%, respectively. Microscopic observations showed notable morphological changes with mycelial collapse, atrophy, and deformation following treatment with the antagonistic filtrates. Moreover, cell membrane permeability results showed increased conductivity in bacteria-treated samples compared to the control. P. polymyxa YF exhibited stable colonization on potato plants and secreted various extracellular enzymes (protease, amylase, and cellulase), along with the synthetic substances with growth-promoting effects, such as siderophores and Indole-3-acetic acid (IAA). Whether it is in the excised tissue inoculation or potted experiment, the negative control showed the highest rank of disease symptoms. In the pot experiment, after YF treatment, physiological parameters showed remarkable changes in plant height, root length, stem thickness, and dry and fresh weight. Compared to blank control, the activities of the four resistant enzymes increased significantly in the P. polymyxa YF treatment group. The upregulation in the P. polymyxa YF group was 4.04, 0.54, 0.46, and 3.10 times, respectively. PCR analysis identified genes in both bacterial strains coding for antimicrobial lipopeptides, including fenB, ituC, and srfAA, which are associated with fengycin, iturin, and surfactin synthesis. These findings demonstrated that P. polymyxa YF has a prominent antagonistic effect on R. solani, suggesting its potential as an effective biological control agent for controlling potato black scurf.